THE IMPACT OF SALES GROWTH AND CASH FLOW FROM OPERATING ACTIVITIES ON FINANCIAL DISTRESS: (AN EMPIRICAL STUDY ON TELECOMMUNICATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2017–2024) - Radick Dwiki Herlambang; Anike Putri (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Along with the increase in internet penetration in Indonesia, which reached 79.5% in 2024, and the growing demand for digital services, the telecommunications sector has experienced significant development. However, several telecommunications companies listed on the Indonesia Stock Exchange, such as PT Telekomunikasi Indonesia Tbk (TLKM), PT Indosat Tbk (ISAT), PT XL Axiata Tbk (EXCL), and PT Smartfren Telecom Tbk (FREN), still show Altman Z’’-Score values below the financial distress threshold. This phenomenon indicates a discrepancy between industry growth and the financial condition of the companies. This study aims to analyze the effect of Sales Growth and Cash Flow from Operating Activities on Financial Distress in telecommunications sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using purposive sampling, resulting in four sample companies with a total of 20 observations. Financial distress is measured using the Altman Z’’-Score, sales growth is measured by the net sales growth ratio, and cash flow from operating activities is measured using the Operating Cash Flow Ratio (OCFR). The results of the multiple linear regression analysis indicate that sales growth has a significant negative effect on financial distress, cash flow from operating activities also has a significant negative effect on financial distress, and both variables simultaneously have a significant influence. Based on Signaling Theory, these findings suggest that strong sales growth and positive operating cash flows serve as positive signals for investors in assessing a company's ability to reduce the risk of financial distress.